The rising temperature trend and elongation of the warm period in summer in the Algerian south-west, 1951–2010 - Oubadi, Miloud; Hamou, Ahmed; Tedim, Fantina (Acta Geographica Lodziensia, 2021)
Several studies indicate that the hot season is lengthening at the expense of the intermediate seasons, and extreme events are becoming more intense and spread out over time. What is the situation in a climate described as very hot? This work aims to examine the evolution of minimum and maximum temperatures in the hot period from June to September during 1951–2010 in the Bechar region, which is classified among the hottest in the world and located in the south-west of Algeria. This study will also focus on the extending of the warm period (the period between the first and the last recording of an extremely hot day). The results showed an evolution of maximum and minimum temperatures, leading to an upward trend in the mid-1990s. There was an average increase of 1°C at the maximum and 0.9°C at the minimum. The warm period experienced a sig-nificant expansion attributed to both the earliest and the latest extremely hot day events.